Adsorption of Ag+ ions using hydroxyapatite powder and recovery silver by electrodeposition. Issue 2 (24th April 2021) - Nam, Pham Thi; Thanh, Dinh Thi Mai; Phuong, Nguyen Thu; Trang, Nguyen Thi Thu; Hong, Cao Thi; Anh, Vo Thi Kieu; Lam, Tran Dai; Thom, Nguyen Thi
Abstract: Nowadays, waste of electrical and electronic apparatuses generated in huge amount surround the earth and has become a global environmental issue. Electronic waste contains large amounts of metal ions, such as Au, Ag, Cu, Pd, Pb and Cd etc., resulting in a threat to the environment, ecosystems and human health. Therefore, removal of metal ions and recovery of precious metals are extremely necessary. Hydroxyapatite material was reported that they can remove heavy metal ions in water with high efficiency. In this work, Ag + ions in water were adsorbed using hydroxyapatite (HAp) powder and recovery silver by electrodeposition. The adsorption efficiency of silver was about 61 % at 50 o C after 60 minutes of contact time. The Ag + adsorption process using HAp powder followed Langmuir adsorption isotherms with the maximum monolayer adsorption capacity of 18.7 mg/g. 60 % of silver can recovery by electrodeposition after 4 hours at the apply current of 10 mA at 50 °C.